Funkcjonowanie Silla w okresie Trzech Królestw. Wybrane aspekty zainspirowane serialem Hwarang (2016) - Kula, Marcin (Instytut Historyczny Uniwersytetu Wrocławskiego, 2023)
Worldwide interest in Korean popular culture, especially television series produced in Seoul, has continued to grow since it first came to the attention of international audiences during the 1990s. This is due, among other things, to the numerous costume productions that not only provide entertainment but alsopo pularise the history of the Korean Peninsula, which affords local politicians a specific tool for conducting modern historical policy.
Keywords: historia Korei; okres Trzech Królestw; Silla; hwarangowie; K-drama; Koreańska Fala; soft historical power